Innovation, digitalization and logistics as factors of regional competitiveness - Agilbayeva А.А.; Khusainova, Zh.S. (BUKETOV BUSINESS REVIEW, 2022)
Object: To identify the impact of innovation, digitalization and logistics as positive factors in the socio-economic system of the region, which are necessary to enhance the competitiveness of regional systems. Methods: The theoretical foundations, dialectical method of cognition, systematic approach, methods of systematic analysis of perception processes. Results: The main significant factors of competitiveness, and their influence and significance on improving the competitiveness of the regional socio-economic system have been studied. The study shows that the regions of Kazakhstan have difficulties with the introduction and development of innovation, and the level of digitalization has not yet taken a leading position. It is demonstrated that factors such as innovation, digitalization and logistics have a high degree of influence on the competitiveness of regions. The growth rates of the volume of innovative products, the growth rates of the share of large and medium-sized industrial enterprises using digital technologies are determined. Logistics as a factor of competitiveness should be considered through the growth rate of the structure of the length of communication routes of roads and railways for public use. Conclusions: A detailed description of digitalization, innovation, logistics in the regions of Kazakhstan allows us to compare the levels of development within the existing process of development of the state. Identification of the dependence of the subjects of economic relations on the proposed research factors makes it possible to determine the parameters of innovative interaction with external and internal elements of the innovation process.